Seminars: Between Students' Perception and Actual Practice - Kasem, Nubough (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The study’s main contribution is highlighting the importance of seminars and their role in helping students improve skills and form their own perspective of the knowledge through experience. More importantly, it gives possible recommendations as to what might be done to have healthy and functional seminars. The importance of this study stems from the importance of seminars as a pedagogical approach that empowers students to take initiative in their own learning. This study is conducted in the English department, mainly third and fourth year students, at Tishreen University to investigate students' perception of seminars and their importance and how they are actually run on the ground. This study follows a descriptive approach, which uses questionnaire for data collection and it is distributed to 60 students. This study concludes that there is a difference between students' perception and their practice on the ground which may indicate that the notion of seminar is good but it is poorly conducted.